Simultaneous functionalization and magnetization of biochar via NH3 ambiance pyrolysis for efficient removal of Cr (VI). (October 2018) - Mian, Md Manik; Liu, Guijian; Yousaf, Balal; Fu, Biao; Ullah, Habib; Ali, Muhammad Ubaid; Abbas, Qumber; Mujtaba Munir, Mehr Ahmed; Ruijia, Liu
Abstract: Enhancing biochar adsorption capabilities and recollection ability is essential for efficient biochar application. In this study, Nitrogen-doped magnetic biochar was prepared via one-step heating of FeCl3 -laden agar biomass under NH3 environment. Synthesized magnetic biochar ABF-N800 shows a maximum Cr (VI) adsorption capacity up to 142.86 mg g −1, outperforming that of magnetic biochar and many other previously reported materials. Moreover, a significant increase of magnetic properties obtained by NH3 ambiance pyrolysis enables easy separation of the adsorbent from the solution after treated with Cr (VI). The physiochemical properties of composites characterized by SEM, EDS, XRD, XPS, VSM, BET surface and pore, Elemental content, and FTIR analysis. The NH3 ambiance pyrolysis confirmed as an efficient process for surface modification, increased magnetic properties and activated N-functional groups. The Langmuir isotherm model and pseudo-second-order model are applicable for describing adsorption behavior. The thermodynamic study shows that the adsorption was spontaneous and endothermic. The present results warrant the application of simultaneous functionalized and magnetized biochar for Cr (VI) contaminated wastewater treatment. Graphical abstract: Image 1 Highlights: N-doped magnetic biochar (ABF-N800 ) synthesized through single-step heating route. Simultaneously nitrogen functional groups and superior magnetic property activated on ABF-N800 . ABF-N800 proven excellent Cr (VI) adsorption competency and recollection ability.